Do age complementarities affect labor productivity? Evidence from German firm level data - Jan Cornelius Peters (Kiel University, Department of Economics, 2017)
In Germany, as in many other European countries, there will be a shift in the workforce age structure in the next decades. The number of older workers will increase, and the number of younger and middle aged workers will decline. This paper provides evidence how the shift in the relative labor supply affects labor productivity, taking into account that differently aged workers are suggested to be imperfect substitutes. Using a cross sectional linked employer-employee data set from 2012, translog cost functions are estimated. To control for the skill level of the workers a nested production structure is applied. This allows to analyze age complementarities within groups of workers that have a comparable skill level. Based on the estimated parameters, pairwise elasticities of complementarity and factor price elasticities are computed. The results indicate that workers that belong to different age groups are complementary factors. But the degree of complementarity differs, depending on the age and the skill level of the workers. The complementarities especially arise between younger and middle aged workers. The highest degree of complementarity is observed between younger and middle aged high skilled labor. Simulating how the expected shift in the age structure affects labor productivity indicates that the productivity of younger and middle aged workers will increase. In contrast, the productivity of older workers will significantly decline caused by their increasing share in the workforce.
Keywords: C31; D24; J11; J31; 330; age complementarities; demographic change; labor-labor substitution; linked employer-employee; translog